Synthesis of Novel Benzofuran‐Gathered C‐2, 4, 6‐substituted Pyrimidine Derivatives Conjugated by Sulfonyl Chlorides: Orally Bioavailable, Selective, Effective Antioxidants and Antimicrobials Drug Candidates. (28th July 2014) - Rangaswamy, Javarappa; Kumar, Honnaiah Vijay; Harini, Salakatte Thammaiah; Naik, Nagaraja
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" id="jhet2209-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>